177 Pro-inflammatory signalling in vascular endothelium: a novel role for camkii in ageing?. (6th June 2015) - McCluskey, Claire; Currie, Susan; Paul, Andrew
Abstract : Nuclear factor-kappa beta (NF-kβ) pro-inflammatory signalling is important in modulating endothelial dysfunction and may be important in vascular dysfunction associated with the ageing process. Recent studies in the heart have highlighted Calcium/calmodulin-dependent protein kinase II (CaMKII) as a novel regulator of NF-kβ signalling. However nothing is known of the role this interaction could play in regulating dysfunction of the vasculature during ageing. Here we (i) characterise NF-kβ signalling in vascular endothelial cells and examine the potential for CaMKII modulation and (ii) determine whether CaMKIIδ expression is altered in ageing. Using human umbilical vein endothelial cells (HUVECs) as an in vitro model system, initial experiments have established that pro-inflammatory NF-kB signalling is activated in response to both tumour necrosis factor α (TNF-α) and interleukin-1β (IL-1β) stimulation. This was shown by a significant reduction in IkBα expression (1.18 ± 0.16 vs. 0.48 ± 0.13, control vs. TNF-α 15 min stimulation, p = 0.008, n = 3); (1.53 ± 0.22 vs. 0.16 ± 0.09 control vs. IL-1β 15 min stimulation, p = 0.004, n = 3) and increased phosphorylation of the p65 subunit (0.69 ± 0.1 vs. 1.22 ± 0.12, control vs. TNF-α 5 min stimulation, p = 0.006, n = 3); (0.54 ± 0.07 vs. 1.86 ± 0.21, control vs. IL-1β 5 min stimulation, p = 0.005, n = 3). We have identified CaMKIIδ as the predominant isoform expressed in HUVECs and shown CaMKII is also activated in response to TNF-α (1.3-fold increase at 10 min stimulation, p = 0.01, n = 3) and IL-1β. Further work has assessed expression of CaMKIIδ in freshly isolated rat aorta. Tissue lysate preparations have compared CaMKIIδ expression in young and aged aortae. Parallel studies in hearts from the same animals have shown CaMKIIδ expression is increased in whole ventricular homogenates prepared from aged versus young hearts (2.3-fold increase, n = 3). These results reflect similar alterations in CaMKIIδ aged hearts as previously observed in models of cardiovascular disease. This highlights the possibility that CaMKII could be pivotal in modulating cardiovascular changes that occur during ageing. Future work will involve selective inhibition of CaMKIIδ in the HUVEC model system by siRNA transfection prior to cytokine stimulation. This will establish involvement of CaMKIIδ in modulation of NF-kB signalling in a vascular endothelial cell line. Studies can then be performed in primary aortic endothelial cells from both young and aged animals to further investigate this interaction and the potential importance in modulating endothelial dysfunction during ageing.